Attitudes and Knowledges of Dairy Farmers toward Forage Canning Tecnology - Mahmud, Ali; Bakhtiar, Ary; Rizki Novanda, Ridha; Ardiansyah, Hendro; Fibriyanti, Dian; Oryza Anantha Helian Thus, Orca; Benson, Yanti (SOCA: Jurnal Sosial Ekonomi Pertanian, 2022)
Nowadays, the problem faced by dairy farmers is that the supply of forage is unstable, while dairy cows required forage intake of 10% of their body weight. In addition, the use of concentrate that was not appropriate affected the quality and quantity of cow's milk. The aims of this research are 1; Analyzing the condition of respondents' characteristics toward the forage canning technology as an alternative feed, 2; Analyzing the attitudes and knowledge of dairy farmers towards forage canning technology as an alternative feed, 3; Formulating a strategy for the development of forage canning technology. The method that used was descriptive analysis which obtained from 62 respondents that taken purposively in 5 Sub-districts, which were Karangploso Sub-district, Ngajum Sub-district, Dau Sub-district, Pujon Sub-district, and Ngantang Sub-district. The research results of knowledge showed that 67.31% of respondents belonged to the category of moderate knowledge, while attitudes showed that 68.43% was included in the category of moderate. Thus, it was concluded that the application of forage canning technology was acceptable and properly implemented in the 5 Sub-districts